Profile of auditory temporal processing in older listeners. - Gordon-Salant S; Fitzgibbons PJ (Journal of Speech, Language & Hearing Research, 1999)
This investigation examined age-related performance differences on a range of speech and nonspeech measures involving temporal manipulation of acoustic signals and variation of stimulus complexity. The goal was to identify a subset of temporally mediated measures that effectively distinguishes the performance patterns of younger and older listeners, with and without hearing loss. The nonspeech measures included duration discrimination for simple tones and gaps, duration discrimination for tones and gaps embedded within complex sequences, and discrimination of temporal order. The speech measures were undistorted speech, time-compressed speech, reverberant speech, and combined time-compressed + reverberant speech. All speech measures were presented both in quiet and in noise. Strong age effects were observed for the nonspeech measures, particularly in the more complex stimulus conditions. Additionally, age effects were observed for all time-compressed speech conditions and some reverberant speech conditions, in both quiet and noise. Effects of hearing loss were observed also for the speech measures only. Discriminant function analysis derived a formula, based on a subset of these measures, for classifying individuals according to temporal performance consistent with age and hearing loss categories. The most important measures to accomplish this goal involved conditions featuring temporal manipulations of complex speech and nonspeech signals.